Linkage disquilibrium analysis on X-chromosome of indigenous breeds of cattle (Bos indicus) adapted to extreme agro-climatic conditions of tropical and temperate ecosystem - Jigyasha Tiwari; Sanjeev Singh; Indrajit Ganguly; S. P. Dixit (Journal of Livestock Biodiversity, 2025)
The present study was undertaken to analyze the breed wise Linkage disequilibrium (LD) decay in indigenous cattle breeds belonging to contrasting landscape (hot semi-arid /arid viz. Hallikar, Kankrej versus cold high altitude viz. Siri and Ladakhi) so as to ascertain the effective number of SNPs required for the preparation of X chromosome specific SNP panel. A total of 46 animals belonging to four different indigenous breeds of cattle were genotyped by using Illumina 777k Bovine HD chip. The LD decay analysis was carried out by using PLINK 1.9 ver. software. The LD between SNP pairs (r2) varied from 0.14 to 0.21 among the breeds with an average of 0.18 for all the breeds. The average inter marker distance on X chromosome in tropical cattle (hot semi-arid /arid) varied from 60 - 100 kb; whereas for temperate cattle it was about 200kb at r2<0.2. Therefore, the effective number of SNPs required for the preparation of X chromosome specific SNP panel was estimated to be about 2,638 for tropical breeds and 791 for temperate breeds. The effective number of SNPs identified in the present study might be helpful in the development of LD maps on X-chromosomes in indigenous breeds of cattle for association studies.